Surge and Scare of Mucormycosis in the Backdrop of COVID-19 Pandemic - Ooha Anyapu; Sreedevi Parvatini; Paparatnam Kalivarapu; Rajani Kuna; Jagadeeswari Suvvari (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Mucormycosis is a rare opportunistic fungal infection. During the second wave of Coronavirus Disease-2019 (COVID-19), a remarkable increase in mucormycosis cases was observed. Diabetes mellitus is an independent risk factor for both mucormycosis and COVID-19. Aim: To assess the incidence of mucormycosis cases in COVID-19 infected and non COVID-19 infected patients and also to assess the related co-morbid conditions during the second wave of COVID-19 pandemic. Materials and Methods: This cross-sectional study was conducted from 15th May 2021 to 15th July 2021 in the Department of Pathology, GGH/Government Medical College, Srikakulam, Andhra Pradesh, India. The study included 63 cases of mucor suspects. The parameters analysed in this study were age, sex, COVID-19 status, co-morbidities, steroid status and radiological findings. A descriptive analysis was made from the data obtained. The information was analysed in data spreadsheets using Microsoft office excel 2010. Results: Out of total 63 mucor suspects, 60 (95.2%) cases tested positive for COVID-19 and 44 (73.3%) cases of them received corticosteroid treatment. Mean age group of 41-50 years with 27 (42.8%) cases with a male preponderance of 49 (77.7%) cases was noted. The most common identified risk factor was diabetes mellitus seen in 22 (34.9%) cases and diabetes associated with hypertension in 14 (22.2%) of the cases. Mucormycosis fungal hyphae were noted in 49 (77.7%) of cases on routine histopathological examination stain and 47 (74.6%) of the cases by special stains for confirmation. Conclusion: In the present study, it was observed that mucormycosis infection was most commonly seen in COVID-19 infected patients in post COVID-19 phase and also in minority of non COVID-19 infected cases with prior debilitating conditions. Therefore, it was concluded that, mucormycosis was positively associated with COVID-19 infected patients who have co-morbidities like diabetes mellitus and history of steroid usage.